Digital Marketing Maturity Models: A Comprehensive Literature Review - Endang Amalia; Feri Sulianta; Ucu Nugraha (International Journal of Multidisciplinary Approach Research and Science, 2026)
Digital marketing has become a critical enabler of organizational transformation, requiring firms to adopt customer-centric strategies and optimize processes in increasingly complex environments. However, the conceptualization and measurement of digital marketing maturity remain inconsistent across the literature. This study addresses this gap by conducting a Systematic Literature Review (SLR) of evolutionary digital marketing maturity models published between 2020 and 2024. Following a four-stage methodological framework—comprising selection and exclusion criteria, database search, quality assessment, and data extraction and synthesis—the review identifies similarities, differences, strengths, and limitations among existing models. The findings reveal that while current models provide useful structures for guiding digital transformation, they lack a precise conceptual definition and standardized measurement framework. The study contributes theoretically by advancing the operationalization of digital maturity and practically by offering executives a framework to assess, benchmark, and monitor progress in digital transformation. Furthermore, it establishes a foundation for future research on the relationship between digital maturity and corporate performance across cultural and regional contexts.